Engagement in dance is associated with emotional competence in interplay with others - Bojner Horwitz, Eva; Lennartsson, Anna-Karin; Theorell, Töres P. G.; Ullén, Fredrik (Frontiers in Psychology, 2015)
This study has explored the relation between dance achievement and alexithymia in a larger Swedish population sample (Swedish Twin Registry) with a study sample of 5431 individuals. Dance achievement (CAQ) was assessed in relation to Alexithymia (Toronto Alexithymia Scale, TAS-20) including the three subscales: Difficulty Identifying Feelings (DIF), Difficulty Describing Feelings (DDF), and Externally Oriented Thinking (EOT). The results show a significant negative association between the TAS subscale (EOT) and creative achievement in dance. A high EOT score corresponds to poor ability to communicate feelings to the environment. There was no consistent association between the other factors DIF and DDF and dance achievement. Dance activity and training seem to be involved in the body’s emotional interplay with others. Embodied cognition, emotional perception, and action are discussed as factors relevant to measuring the skill of a dancer.